Amazon: Cloud Computing Services and Security - Karthika, J.P; Vennila, P (International Journal of Computer Sciences and Engineering, 2025)
Cloud Computing is a set of IT services that are provided to a customer over a network on a leased basis and with the ability to increase or down their service requirements. Cloud Computing provides the services to the third party provider who owns the infrastructure. It holds the probable to purge the requirements for setting up of high-cost computing infrastructure for IT-based solutions and services that the industry uses. Many industries, banking, healthcare and education are moving towards the cloud due to the efficiency of services provided by the pay-per-use pattern based on the possessions such as processing power used, transactions carried out, bandwidth consumed, data transferred, or storage space occupied. This paper mainly focuses on three cloud service models, frequently referred to as Software as a Service (SaaS), Platform as a Service (PaaS) and Infrastructure as a Service (IaaS). This also discusses with example some major cloud service providers in order to show that how cloud computing will make the business world simpler, more proficient and more specialized